PENGEMBANGAN INOVASI ORGANISASI BERBASIS HUMAN CAPITAL, SHARING KNOWLEDGE DAN PEMBELAJARAN ORGANISASIONAL - Kesi Widjajanti; Widodo . (Jurnal Ekonomi dan Bisnis, 2014)
This study aims to analyze the relationship of organizational learning, knowledgesharing, knowledge sharing and its effect on human capital and organizationalinnovation. Then create a model for organizational innovation-based development ofhuman capital, knowledge sharing and organizational learning SMEs in SemarangRespondents stui entrepreneurs are leaders trained partners with a numberof 150 sampling purposive sampling method. Then to analyze the data inthis study used the Structural Equation Modeling (SEM) with AMOS softwareThe results of this study suggest that innovation-based organizations to develop human capital, knowledge sharing and organizational learning, organizational innovation first built with human capital that is influenced by increasing organizational learning. The second innovation is built with a knowledge sharing organization. The third innovation is built with human capital organization.